Comparison of efficacy profiles for minimum lethal concentrations (MLCs) of some commonly used commercial hospital microbicidal detergent-disinfectant products for disinfectants and sporicidal activity. - Deshaies, Francis; Ahmad, Darakhshan; Massicotte, Richard; Pichette, Gilbert; Belhumeur, Pierre; Mafu, Akier Assanta (International Journal of Infection Control, 2012)
In an effort to evaluate and control the potential hazard and inherent risk of environmental transmission and spread of nosocomial infections by contact with hitherto “non-critical” inanimate/environmental surfaces in the hospital/ healthcare facilities (commode, bed, bowl of toilet etc.), the microbicidal efficacies of six disinfectants products of the most commonly used commercially available detergent-disinfectants (one chlorine-based, one phenol-based, two quaternary ammonium compounds (QACs), generation 3 and generation 4 and, two hydrogen peroxide-based) were evaluated at different concentrations using use-dilution method for evaluating the minimum lethal concentrations (MLCs). Results from these in vitro germicidal exposure experiments indicate that all six disinfectants tested were at the MLCs of these disinfectants in proportion to the recommended strengths varied significantly and yielded very different performance values for different test strains. This knowledge could prove to be of significance in assessing the risks associated with the use, and the incidental failure thereof, of different disinfectants used in the healthcare facilities. The results from our study highlights differences in the activity of germicides against different bacterial strains and indicate that the choice of disinfectant agents and the hospital decontamination protocols can markedly affect the prevalence and environmental distribution of pathogens, and that this could be, to a certain extent, better managed if a proper assessment of the risk associated with the use of disinfectants at off-recommended strengths conditions is taken into account in providing guidance towards and seeking satisfactory resolutions to the incidence of breach of manufacturers’ recommendations.